2016
DOI: 10.1038/srep25469
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain bases of sphingolipids are transported into cells via the acyl-CoA synthetases

Abstract: Transport of dietary lipids into small-intestinal epithelial cells is pathologically and nutritionally important. However, lipid uptake remains an almost unexplored research area. Although we know that long-chain bases (LCBs), constituents of sphingolipids, can enter into cells efficiently, the molecular mechanism of LCB uptake is completely unclear. Here, we found that the yeast acyl-CoA synthetases (ACSs) Faa1 and Faa4 are redundantly involved in LCB uptake. In addition to fatty acid-activating activity, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Dietary SM, in particular, is known to dose-dependently reduce the intestinal absorption of cholesterol, TG, and fatty acids in rodents [10]. Products of SM digestion, such as ceramides and sphingosine, also inhibit cholesterol and fatty acid absorption [59][60][61]. Compared to SM derived from egg yolk, SM from milk has been shown to have stronger effects on inhibiting the intestinal absorption of fat and cholesterol in rats, potentially due to stronger hydrophobic interactions between milk SM and other lipids [62].…”
Section: Effects On Intestinal Lipid Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary SM, in particular, is known to dose-dependently reduce the intestinal absorption of cholesterol, TG, and fatty acids in rodents [10]. Products of SM digestion, such as ceramides and sphingosine, also inhibit cholesterol and fatty acid absorption [59][60][61]. Compared to SM derived from egg yolk, SM from milk has been shown to have stronger effects on inhibiting the intestinal absorption of fat and cholesterol in rats, potentially due to stronger hydrophobic interactions between milk SM and other lipids [62].…”
Section: Effects On Intestinal Lipid Absorptionmentioning
confidence: 99%
“…In vitro studies suggest that SM in mixed micelles can reduce TG hydrolysis by inhibiting human pancreatic lipase-colipase activity [65,66]. Long-chain bases of SLs and long-chain fatty acids also have been reported to compete with each other for cellular uptake, since they both utilize acyl-CoA synthetases [61].…”
Section: Effects On Intestinal Lipid Absorptionmentioning
confidence: 99%
“…We recently revealed the FA transporter family (also known as acyl-CoA synthetase family) members Faa1 and Faa4 are involved in importing both LCBs and long-chain FAs (30). We found here that Rsb1 facilitated export of DHS and 1-hexadecanol, but not palmitic acid (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…and Faa4 (7,37). We found that an exogenous supply of sphingosine, a major LCB in mammals, can also rescue the growth of…”
Section: E Effect Of Remodeling Of the Structure Of Longchain Bases mentioning
confidence: 77%